(untitled) (Biological Sciences - PJSIR, 2023)
Many pests are known to damage cucurbitaceous vegetables in Bangladesh but the abundance and host preference of the cucumber moth, Diaphania indica (Crambidae: Lepidoptera) has not been studied previously. Efforts were made to study biology, natural abundance and extent of damage and the influence of seasonal parameters on D. indica. The life cycle duration of D. indica was 17.4 ± 0.36 days, where the incubation period, larval period and adult longevity were 3.5 ± 0.16, 12.4 ± 0.16 and 3.5 ± 0.16 days respectively. Their abundance was high in the summer season and positively correlated with the temperature increases. Snake gourd followed by ridge gourd was the preferred and bitter gourd was the less preferred summer vegetable. In contrast, significantly lower leaf infestations and larval presence were observed in the winter vegetables. The findings extrapolate the potential of D. indica as a threat to summer cucurbitaceous vegetables in the future.